Corrigendum: Compound Dihuang Granule inhibits nigrostriatal pathway apoptosis in Parkinson’s disease by suppressing the JNK/AP-1 pathway - Wang, Li; Yang, Yu-fang; Chen, Long; He, Zhu-qing; Bi, Dian-yong; Zhang, Lei; Xu, Yan-wu; He, Jian-cheng (Frontiers in Pharmacology, 2023)
Graphical Abstract The graphical abstract of this study.